(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Temporomandibular joint disorders (TMDs) are among the most common disorders in the maxillofacial region which usually present with joint pain, decreased jaw mobility, joint clicking, headache, tinnitus, neck pain etc. There are different modalities of treatment used for the TMDs. These include some conservative and surgical procedures. The main aim is to improve the jaw function and reduction of joint pain. Arthroscopy is a modern diagnostic and effective therapeutic procedure for the TMDs. Objective: To assess the outcome of arthroscopic lavage of Temporomandibular Joint (TMJ) in terms of improvement of jaw function and joint pain in patients suffering from TMDs. Materials and Methods: This prospective study was carried out at the department of Oral and Maxillofacial Surgery, Military Dental Centre, Combined Military Hospital of Dhaka Cantonment from 01 October 2014 to 31 March 2016. Patients were selected consecutively having TMDs and unresponsive to conservative nonsurgical therapy. Total thirty patients of TMDs were selected for study and all the patients were treated with arthroscopic lavage. Objective data were collected including, inter incisal opening, lateral excursion, deviation on opening, tenderness on palpation. A questionnaire in the form of visual analogue scale relating to pain, joint clicking and Jaw mobility were completed by each patient at 1 week,1 month and 6 months post operatively. Results: Among thirty patients, 10 patients were male and 20 patients were female. Mean age of the patient was 42.6±5.79 years. Maximum patients were in the age group of 41-45 years. There was statistically significant improvement in maximum incisal opening and pain score. There was also reduction in Joint clicking and tenderness in maximum patients. Conclusion: The findings of the present study suggested potential utility of arthroscopic lavage in the management of TMDs. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 88-93